PEMBUATAN APLIKASI PEMESANAN BANNER DI WARNA PRINT KOTA CIMAHI - Johni S. Pasaribu (Universitas Widyatama, 2021)
Nowadays technology is developing very fast, including information and communication technology. For that we need fast steps in following it. Information and communication technology has entered all aspects of life, including the business world. This is because the work assisted by information technology can minimize errors and even losses that will occur. Warna Print is a company engaged in the printing sector, which serves banner designs and banner printing and is currently facing problems in the field of ordering. The banner ordering system used in Warna Print is still done conventionally. For example, in recording orders, making order invoices to taking orders and transaction reports, they still rely on recording on notes. This of course can cause loss or damage to the order data and sales transactions. With the design of this application will be able to help expedite the transaction process on Color Print. The design of this application uses the Netbeans IDE with the Java programming language and the MySQL database program. This application has guaranteed security, because only owners and employees who have a username and password can access this application. In addition, the error rate in recording orders is very small, because each customer receives a different transaction number, so as to minimize errors on the transaction report.